Ethical Engineering for International Development and Environmental Sustainability - Hersh, Marion (Springer, 2015)
Ensuring that their work has a positive influence on society is a responsibility and a privilege for engineers, but also a considerable challenge. This book addresses the ways in which engineers meet this challenge, working from the assumption that for a project to be truly ethical both the undertaking itself and its implementation must be ethically sound.